2021
DOI: 10.2334/josnusd.21-0051
|View full text |Cite
|
Sign up to set email alerts
|

Sedation outcomes for remimazolam, a new benzodiazepine

Abstract: Remimazolam is a new ultrashort-acting benzodiazepine with fast onset, quick recovery, and few side effects, such as hypotension and respiratory depression. It is expected to be safe and effective for a wide range of patients undergoing intravenous sedation for dental procedures. The aim of this literature review was to evaluate clinical and sedation outcomes for remimazolam, including method of administration, level of sedation at the dose required, and clinical adverse events. An electronic literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…Although it has a rapid onset of action and a very short half-life, it precipitates more adverse events, notably possible hypotension, respiratory depression, bradycardia, and pain upon injection. Therefore, there is a need for safer sedatives while ensuring their efficacy [ 35 ]. Clinical studies comparing efficacy and safety of remimazolam vs. propofol for procedural sedation suggested that remimazolam was non-inferior in terms of sedative efficacy and exhibited better safety profile than that of propofol [ 32 , 34 , 36 ].…”
Section: Clinical Applications Of Remimazolammentioning
confidence: 99%
“…Although it has a rapid onset of action and a very short half-life, it precipitates more adverse events, notably possible hypotension, respiratory depression, bradycardia, and pain upon injection. Therefore, there is a need for safer sedatives while ensuring their efficacy [ 35 ]. Clinical studies comparing efficacy and safety of remimazolam vs. propofol for procedural sedation suggested that remimazolam was non-inferior in terms of sedative efficacy and exhibited better safety profile than that of propofol [ 32 , 34 , 36 ].…”
Section: Clinical Applications Of Remimazolammentioning
confidence: 99%
“…It has a high affinity and selectivity for the benzodiazepine site on the GABA receptors [ 21 - 22 ]. Furthermore, the metabolite of remimazolam has a lower affinity for the benzodiazepine receptors than the metabolite of midazolam, α-hydromidazolam [ 23 ]. The addition of a carboxylic ester in the benzodiazepines makes it receptive to tissue esterases (CES), resulting in a pharmacologically inactive metabolite, CNS-7054.…”
Section: Reviewmentioning
confidence: 99%
“…8 Remimazolam is a new benzodiazepine that has recently been found to provide good outcomes in conscious sedation in dentistry due to its ultrashort-acting properties. 9 Remimazolam, as its name suggests, combines the properties of midazolam and remifentanil and it acts on the gamma aminobutyric acid (GABA) receptors, but its ester-linked side chain to the diazepine ring makes it an ultrashort-acting sedation drug that is metabolised rapidly to inactive metabolites by liver tissue esterases. 9 Also, the hepatic drug-metabolising enzyme cytochrome P450 (CYP) is not involved in the metabolism, similar to that of remifentanil.…”
Section: Introductionmentioning
confidence: 99%
“…9 Remimazolam, as its name suggests, combines the properties of midazolam and remifentanil and it acts on the gamma aminobutyric acid (GABA) receptors, but its ester-linked side chain to the diazepine ring makes it an ultrashort-acting sedation drug that is metabolised rapidly to inactive metabolites by liver tissue esterases. 9 Also, the hepatic drug-metabolising enzyme cytochrome P450 (CYP) is not involved in the metabolism, similar to that of remifentanil. 10 These combined properties therefore make remimazolam a drug of fast onset, high clearance, short half-life, and few side-effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation